Clinical and economic assessment of feasibility of using quadritherapy in patients with reduced ejection fraction chronic heart failure in medical organizations of the Moscow Region - A. D. Ermolaeva; T. N. Ermolaeva; K. A. Kokushkin (Фармакоэкономика)
Objective: assessment of feasibility of using four-component drug therapy for patients with chronic heart failure with reduced ejection fraction (CHFrEF) in medical organizations of the Moscow Region (MR).Material and methods. Clinical and economic analysis of combined standard therapy with angiotensin-converting enzyme inhibitors, beta-blockers, and mineralocorticoid-receptor antagonists in combination with dapagliflozin (a sodium-glucose cotransporter 2) in the treatment of patients with CHFrEF was carried out. The effectiveness criteria were the number of prevented cardiovascular (CV) deaths and the percentage of the contribution to the achievement of the target indicator to reduce mortality from circulatory diseases within the framework of the regional program “Health care development”. In order to determine the economic feasibility of quadritherapy, direct medical costs for the implemented technology were calculated, the cost of one prevented CV death was determined based on the values of the number needed to treat (NNT) indicator. Budget impact analysis was performed which allowed to build two analytical models. Results. It was shown that the use of quadritherapy can significantly contribute to achieving the target indicator by additionally preventing 512 CV deaths by 2024, which will make it possible to fulfill up to 74.74% of the indicator set by the MR state program “Health care of the Moscow Region” (451.4 persons per 100 thousand population). Using quadruple therapy in 1000 target patients during the first year will prevent 11 CV deaths (NNT 90 persons). The cost of one prevented CV death was 3.860 million rubles. The budget impact analysis made it possible to determine that when CHF patients switch from standard treatment regimens to quadritherapy, including in combination with a drug of the angiotensin/neprilysin receptor inhibitor group (valsartan + sacubitril), this will entail an increase in healthcare system budget costs by 18.8%.Conclusion. The results demonstrate that the standard therapy in combination with the innovative drug dapagliflozin leads to a proven reduction in mortality from circulatory diseases. This technology is a cost-effective approach to organizing medical care for adult patients with CHFrEF on the MR territory.